Integrating Intelligent-Technological Pedagogical and Content Knowledge (Intelligent-TPACK) and Tripartite Models to Examine Teachers’ Knowledge and Attitudes Toward Artificial Intelligence (AI) - Mina Alhiane; Youssef Nafidi (Bumi Publikasi Nusantara, 2026)
Artificial Intelligence (AI) technologies have transformed educational practices, yet their effective integration in K–12 classrooms, particularly in the Moroccan context, remains underexplored. This study aims to examine teachers’ knowledge and attitudes toward AI integration using the Intelligent-Technological Pedagogical and Content Knowledge (Intelligent-TPACK) framework and the Tripartite Model of Attitudes. A total of 204 Moroccan teachers participated in a survey. Collected data were analyzed through Exploratory and Confirmatory Factor Analyses, followed by Structural Equation Modeling (SEM) using SmartPLS. Results confirmed the validity of both models and revealed that Intelligent Techno-Pedagogical Knowledge (ITPK) is the strongest predictor of teachers’ affective, behavioral, and cognitive attitudes toward AI. Ethical considerations significantly influenced cognitive attitudes, indicating reflective rather than resistant views toward AI adoption. These findings suggest that integrating pedagogical and ethical awareness into teacher training programs can foster positive attitudes and responsible AI use, supporting national education reforms aligned with Sustainable Development Goal 4 on quality education.